1999
DOI: 10.1074/jbc.274.40.28682
|View full text |Cite
|
Sign up to set email alerts
|

The Proximal Portion of the COOH Terminus of the Oxytocin Receptor Is Required for Coupling to Gq, but Not Gi

Abstract: As the oxytocin receptor plays a key role in parturition and lactation, there is considerable interest in defining its structure/functional relationships. We previously showed that the rat oxytocin receptor transfected into Chinese hamster ovary cells was coupled to both G q/11 and G i/o , and that oxytocin stimulated ERK-2 phosphorylation and prostaglandin E 2 synthesis via protein kinase C activity. In this study, we show that deletion of 51 amino acid residues from the carboxyl terminus resulted in reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(20 citation statements)
references
References 67 publications
1
18
0
1
Order By: Relevance
“…It is interesting to note that this PAR2 mutant showed the same defective internalization and desensitization as the OTR-GFP-cav2 mutant described here. Since human OTR activates the p42/44 and p38 MAPK pathways via both sensitive and insensitive PTX signalling pathways (Hoare et al, 1999;Ohmichi et al, 1995;Strakova et al, 1998), it can be hypothesized that OTR localized in caveolar domains activate the MAP kinase in a Ras-dependent pathway leading to the activation and translocation of ERK1/ERK2 and cell proliferation, whereas the inhibition of cell growth may be associated with PLC-and PCK-dependent and Ras-independent activation. Experiments using inhibitors of the dierent signalling pathways potentially involved in MAPK activation by OTR-GFP-cav2 or WT OTR-GFP are currently under way in order to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that this PAR2 mutant showed the same defective internalization and desensitization as the OTR-GFP-cav2 mutant described here. Since human OTR activates the p42/44 and p38 MAPK pathways via both sensitive and insensitive PTX signalling pathways (Hoare et al, 1999;Ohmichi et al, 1995;Strakova et al, 1998), it can be hypothesized that OTR localized in caveolar domains activate the MAP kinase in a Ras-dependent pathway leading to the activation and translocation of ERK1/ERK2 and cell proliferation, whereas the inhibition of cell growth may be associated with PLC-and PCK-dependent and Ras-independent activation. Experiments using inhibitors of the dierent signalling pathways potentially involved in MAPK activation by OTR-GFP-cav2 or WT OTR-GFP are currently under way in order to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that OTRs couple to Ga q/11 alone, to Ga i and Ga q/11 , or to Ga i and Ga s in myometrial cells (Hoare et al, 1999;Strakova and Solo, 1997), and that the inhibitory eects on the proliferation of breast cancer and glial cells are associated with an increase in intracellular cAMP levels (Cassoni et al, 1997(Cassoni et al, , 1998. Furthermore, since OT promotes the synthesis of prostaglandins in a number of cell systems, some OTmediated eects on cell proliferation may be indirectly mediated by an autocrine/paracrine loop involving the activation of Ga s -coupled prostaglandin receptors, thus leading to increased cAMP production and the inhibition of proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The recent crystal structures of the human ␤ 2 -adrenergic receptor have an 8th helix underlying the membrane perpendicular to the transmembrane helices which is stabilized by a hydrophobic surface (40 -43). In fact, an 8th helix is thought to be present in most, if not all, rhodopsin-like 7TMRs and play a role in signaling by directly interacting with heterotrimeric G-protein subunits (43)(44)(45)(46)(47)(48)(49), although roles in ligand binding have also been reported (50). The 8th helix of D6 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although for some GPCRs, Hx8 appears dispensable for signaling (26), the importance of Hx8 in G-protein interaction has been shown, e.g. for the oxytocin receptor (27), bradykinin receptors (28), the angiotensin II receptor type 1A (29), the leukotriene B4 receptor (30), and the ␤ 1 -adrenergic receptor (31). Moreover, the N-terminal portion of Hx8 of the protease-activated receptor PAR1 was found to be involved in coupling to G␣ q , through a network of H-bond and ionic interactions, connecting Hx8 to the conserved NPXXYX 5,6 F motif on TM7 and also to the adjacent intracellular loop 1 (32).…”
Section: Discussionmentioning
confidence: 99%